Philosophical Re-examination of Labor Theory Beyond Economic Dimensions in Trademark Jurisprudence - Azizah, Siti Nur; Thio, Ricky (LifeSciFi, 2025)
This research reconstructs the understanding of John Locke’s doctrine, which has conventionally been regarded as focusing solely on economic dimensions within property theory. Conventional scholarship positions Locke as a philosopher who neglects moral rights, in contrast to Hegel, who acknowledges both moral and economic dimensions. This research challenges this dichotomy by revealing that Locke actually paid significant attention to moral aspects within his labor theory, particularly in the context of trademark protection. The research methodology employs a normative juridical approach with in-depth philosophical analysis of Locke’s primary works, particularly Two Treatises of Government, and compares these with implementation in contemporary Indonesian trademark jurisprudence. The discussion finds that Locke’s labor theory contains strong moral foundations through concepts of natural law and human dignity. The research conclusion demonstrates that Locke’s doctrine genuinely integrates moral and economic rights coherently, providing more comprehensive philosophical justification for trademark protection. It is recommended that intellectual property law academics and practitioners abandon reductive interpretations of Locke and adopt a holistic understanding that recognizes moral dimensions within Indonesia’s trademark protection system.